Contemporary South Korean economy challenges and prospects - Chiang,Min-Hua,1978- (Singapore World Scientific Publishing Co. Pte. Ltd., 2017)
"This book provides an analytical overview of key issues in contemporary South Korean economy. The timely and in-depth study presented in the book examines the main reasons behind South Korea's economic slowdown in recent years, the economic and social impact following chaebol's growing business expansion, free trade agreements with China and the United States, the development of income inequality, the ageing demography and the Korean government's policy response to overcome the current economic difficulties."--Provided by publisher.
Keywords: Korea(South) -- Economic conditions -- 21st century; Economic development -- Korea(South) -- History -- 21st century; Income distribution -- Korea(South).; International economic relations